Культура як складова суспільного та особистісного розвитку - Малахова, А. А. (ХНУРЕ, 2021)
It is known that the genesis of culture is not very simple and is associated with the historical development of society. At the same time, quite peculiar and cultural knowledge that relate to many areas of development of society. However, without cultural knowledge, one cannot talk about a civilized society, a person, we do not consider the progress of humanity in the future.
Keywords: культура; українознавство